2018
DOI: 10.1016/j.jvs.2018.05.232
|View full text |Cite
|
Sign up to set email alerts
|

Current evidence in predictors of aortic growth and events in acute type B aortic dissection

Abstract: Among several predictors of aortic growth and events in acute type B aortic dissection, controversial and even conflicting results have been described. Consistent evidence has been demonstrated only for two predictors: aortic size at presentation is associated with adverse events and total FL thrombosis has a protective role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
63
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 62 publications
1
63
0
2
Order By: Relevance
“…Current treatment protocols and surgical criteria are largely based on anatomic variables, the most important of which is maximum aortic diameter [ 7 ]. Aortic diameter is a simple metric, and has a direct relationship with tensile wall stress (i.e., Law of Laplace).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Current treatment protocols and surgical criteria are largely based on anatomic variables, the most important of which is maximum aortic diameter [ 7 ]. Aortic diameter is a simple metric, and has a direct relationship with tensile wall stress (i.e., Law of Laplace).…”
Section: Discussionmentioning
confidence: 99%
“…Aortic diameter is a simple metric, and has a direct relationship with tensile wall stress (i.e., Law of Laplace). However, in a recent systematic review of growth in TBAD, maximal aortic diameter was associated with growth in only ~ 50% of studies, highlighting the need for better risk stratification tools [ 7 ]. While our results support the association between baseline diameter and aortic growth we also found that FLEF and FL ΔP max provided additional predictive value over baseline diameter alone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Review of type B dissections suggests that the size of the aorta at presentation, the size of the false lumen compared with true lumen, and the number of branches arising from the false lumen may be indicators of poor outcome if untreated. 5,6 To approach the treatment of the descending aorta, we must consider conditions at the time of presentation. The modified frozen elephant trunk has appeal when the stent can be placed to exclude any entry within the arch.…”
mentioning
confidence: 99%